Novel Insights into MSK1 Phosphorylation by MRKβ in Intracerebral Hemorrhage-Induced Neuronal Apoptosis. Issue 6 (June 2019) - Gong, Peipei; Jiang, Rui; Yao, Junzhong; Yao, Qi; Xu, Xide; Chen, Jian; Shen, Jianhong; Shi, Wei
Neuronal apoptosis is regarded as one of the most important pathophysiological changes of intracerebral hemorrhagic (ICH) stroke—a major public health problem that leads to high mortality rates and functional dependency. Mitogen-and stress-activated kinase (MSK) 1 is implicated in various biological functions in different cell types, including proliferation, tumorigenesis and responses to stress. Our previous study showed that MSK1 phosphorylation (p-MSK1) is related to the regulation of LPS-induced astrocytic inflammation, and possibly acts as a negative regulator of inflammation. In this study, we identified a specific interaction between MSK1 and MRKβ (MLK-related kinase)—a member of the MAPK pathway—during neuronal apoptosis. In an ICH rat model, western blotting and immunohistochemical analysis revealed that both MRKβ and phosphorylation of MSK1 (p-MSK1 Ser376) were significantly upregulated in cells surrounding the hematoma. Triple-immunofluorescent labeling demonstrated the co-localization of MRKβ and p-MSK1 in neurons, but not astrocytes. Furthermore, MRKβ was partially transported into the nucleus, and interacted with p-MSK1 in hemin-treated neurons. Immunoprecipitation showed that MRKβ and p-MSK1 exhibited an enhanced interaction during the pathophysiology process. Utilizing small interfering RNAs to knockdown MRKβ or MSK1, we verified that MSK1 Ser376 is a phosphorylation site targeted by MRKβ. We also observed that the phosphorylation of NF-κB p65 at Ser276 was mediated by the MRKβ-p-MSK1 complex. Furthermore, it was found that the neuronal apoptosis marker, active caspase-3, was co-localized with MRKβ and p-MSK1. In addition, flow cytometry analysis revealed that knockdown of MRKβ or MSK1 specifically resulted in increased neuronal apoptosis, which suggested that the MRKβ-p-MSK1 complex might exert a neuroprotective function against ICH-induced neuronal apoptosis. Taken together, our data suggest that MRKβ translocated into the nucleus and phosphorylated MSK1 to protect neurons via phosphorylation of p65—a subunit of nuclear factor κB.